Synthesis of 2, 2′-hindered pyridine containing semifluorinated polytriazoles and investigation for low-temperature proton exchange membrane application with enhanced oxidative stability. (5th August 2020) - Roy, Sambit; Ghorai, Arijit; Komber, Hartmut; Voit, Brigitte; Banerjee, Susanta
Graphical Abstract: Abstract: A series of new sulfonated copolytriazoles were prepared from a novel fluorinated diazide monomer with pyridine moiety to enhance both the oxidative stability and proton conductivity of proton exchange membranes. These proton donor–acceptor based copolymers and homopolymers were synthesized by click cycloaddition polymerization of the dialkyne monomer 1, 2, 4, 5-tetrafluoro-3, 6-bis(prop-2-yn-1-yloxy)benzene (TFAK) with or without the pyridine containing diazide monomer 2, 2′-bis(4-(4-azidophenoxy)-3-(trifluoromethyl)phenyl)pyridine (PYFAZ) and the sulfonated diazide monomer 4, 4′-diazido-2, 2′-stilbenedisulfonic acid disodium salt (DSSAZ). 1 H, 13 C, and 19 F NMR, in addition to FTIR analyses, confirm the formation of polytriazoles with a graded degree of sulfonation between 70% and 100%. The solution cast membranes were flexible and showed high chemical, thermal and mechanical properties. Inclusion of pyridine moiety proved to play a significant role in increasing peroxide stability by quenching hydroxyl and hydroperoxide radicals and forming pyridine-N-oxide, which was analyzed by EPR and FTIR spectroscopy. The presence of pyridine moiety also enhanced proton conductivity owing to the presence of the weakly basic nitrogen in pyridine that acts as a proton hopping site. AFM and HR-TEM images of the membranes indicated the formation of phase-separated morphology and that became more pronounced with the increase in the degree of sulfonation. The membranes obtained from PYFTSH-90 copolymer exhibited proton conductivity of 125 mS cm −1 at 80 °C, which is comparable to Nafion-117. The proton conductivity of PYFTSH-90 was further increased to 139 mS cm −1 at 90 °C. Thus, three significant objectives have been fulfilled in this work, namely (i) high proton conductivity, (ii) high hydrolytic stability, and (iii) high peroxide stability. These properties demonstrate that these copolymer membranes are potentially highly suitable for application in low-temperature proton exchange membrane fuel cell (PEMFC).